1997
DOI: 10.1111/j.1365-3016.1997.tb00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐economic deprivation associated with acute rheumatic fever. A hospital‐based case‐control study in Bangladesh

Abstract: There are few studies on the relationship between socio-economic factors and rheumatic fever (RF) in the populations where the burden of both socio-economic deprivation and RF is still very high. The aim of this study is to assess the association between some socio-economic factors and RF by examining data available from a RF hospital in Bangladesh. We have reviewed the medical records of patients presenting with manifestations suggestive of RF during a 1-year period. From the patients who showed group A beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Low income, poor living, and substandard housing (especially crowding) are risk factors associated with outbreaks of the disease [3]. Climatic factors such as cold and humidity are implicated in the incidence of acute rheumatic fever, which may be important in the spread of the infection with Streptococcus.…”
Section: Epidemiologymentioning
confidence: 99%
“…Low income, poor living, and substandard housing (especially crowding) are risk factors associated with outbreaks of the disease [3]. Climatic factors such as cold and humidity are implicated in the incidence of acute rheumatic fever, which may be important in the spread of the infection with Streptococcus.…”
Section: Epidemiologymentioning
confidence: 99%
“…[7][8][9][10][11] This view is supported by research showing that ARF is associated with socio-economic and living conditions. 12,13 Previous studies have identified associations between ARF/RHD and poor housing conditions, [14][15][16][17] sometimes including home crowding. 12,13,18,19 It is possible that cold, damp living conditions promote GAS infection by weakening immune and respiratory defences.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…Poverty may feed indirectly into other factors that may impact on RF, such as crowding, housing, nutrition, parental unemployment and poor access to health care. [12][13][14][17][18][19]21,23,24,26,33,36,37,[39][40][41] Since the publication of the guideline, the New Zealand Child & Youth Epidemiology Service in its Indicator Handbook have linked the risk of RF to high levels of deprivation using the New Zealand Deprivation Index (see earlier), which is based on household income, access to telephone and car, education level and housing. 3…”
Section: Povertymentioning
confidence: 99%
“…Many published studies were found on the association between crowding and RF. 12,[15][16][17][18][19][20][22][23][24][25][26][27][29][30][31][32][34][35][36][37]39,[41][42][43][44][45][46][47][48] There is evidence from comparative studies of a link between crowding in the home and RF information on household crowding is available by region in NZ with considerable geographic variation. Auckland is the most crowded region.…”
Section: Crowdingmentioning
confidence: 99%